Assessment of flood risks territories in the context of agricultural land management of amalgamated territorial community - Danko, K.; Butenko, Y. (Land Management, Cadastre and Land Monitoring, 2022)
Abstract. The implementation of land reform and the introduction of the land market encourages the use of highly effective approaches to agricultural land management in the face of climate change. Agriculture is vulnerable to the effects of climate change due to extreme weather events, which intensify land degradation processes, such as water erosion and flooding. In such circumstances, the application of approaches to assessing the risks of flooding in the context of agricultural land management of territorial communities is relevant. On the example of Slavska TG and Skolivska TG, the risk assessment of flooding of the Opir River and Stryi rivers (at the confluence of the Opir River) was carried out. The research was performed on the normative provisions of the national legislation of Ukraine, as well as Directive 2007/60 / EC and its guiding documents. The flood zones of the territories within Slavska TG and Skolivska TG, the areas of relevant floods and the amount of potential losses for agricultural lands under different flood scenarios have been identified. It is proposed to develop and implement a number of measures to minimize the negative effects and losses associated with land flooding. Prospects for the application of the results in the development of land management documentation are considered. Key words: flood risk assessment, probability of exceedance, agricultural lands, Opir river, Slavska TG, Skolivska TG.